Personality and Occupational Accidents: Bar Benders in Guangdong Province, Shenzhen, China - Sing, Michael; Love, Peter; Fung, I.; Edwards, D. (American Society of Civil Engineers, 2014)
Limited research has been undertaken to explore how Chinese construction workers’ personality affects their safety behavior. Inappropriate behavior on-site can instigate serious accidents, injuries, or fatality as well as incur significant costs and loss of corporate reputation. To address this dearth within the extant literature, this paper uses Eysenck Personality Questionnaire to examine the complex relationship between the personality of Chinese construction workers (especially, bar benders) and occupational accidents. A significant relationship between personality, unsafe behaviors, and the extent of injury was identified. Using the results generated, a series of practical recommendations are proffered to reinforce behavioral safety training (and reduce accidents on-site), including suggestions for conducting training programs that can be tailored to construction workers with different personality traits.